2024
DOI: 10.1172/jci176411
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral second dose improves antibody responses to a 2-dose mRNA vaccination regimen

Sedigheh Fazli,
Archana Thomas,
Abram E. Estrada
et al.

Abstract: BACKGROUND.Vaccination is typically administered without regard to site of prior vaccination, but this factor may substantially affect downstream immune responses. METHODS.We assessed serological responses to initial COVID-19 vaccination in baseline seronegative adults who received second-dose boosters in the ipsilateral or contralateral arm relative to initial vaccination. We measured serum SARS-CoV-2 spike-specific Ig, receptor-binding domain-specific (RBD-specific) IgG, SARS-CoV-2 nucleocapsid-specific IgG,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…In contrast, Fazli et al reported that contralateral boosting (n = 440) with BNT162b2 mRNA vaccine was associated with slightly higher spike-and RBD-specific serum IgG titers compared to ipsilateral boosting (n = 507), and this effect increased over time from a 1.1-fold to a 1.4-fold effect by 14 months. Contralateral boosting also resulted in increases (1.3-fold to 4.0-fold) in neutralizing antibody titers against B.1.1.529 at 8-and 14-months, with lesser effects against the WA1/2020 D614G strain (no difference at 8-months and 2-fold difference at 14 months) 23 . fate-mapping studies in mice, which showed that recruitment of antigen-experienced memory B cells to secondary GCs is inefficient 38,39 , as the progeny of primed GC B cells account for only a subset of total GCBs.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In contrast, Fazli et al reported that contralateral boosting (n = 440) with BNT162b2 mRNA vaccine was associated with slightly higher spike-and RBD-specific serum IgG titers compared to ipsilateral boosting (n = 507), and this effect increased over time from a 1.1-fold to a 1.4-fold effect by 14 months. Contralateral boosting also resulted in increases (1.3-fold to 4.0-fold) in neutralizing antibody titers against B.1.1.529 at 8-and 14-months, with lesser effects against the WA1/2020 D614G strain (no difference at 8-months and 2-fold difference at 14 months) 23 . fate-mapping studies in mice, which showed that recruitment of antigen-experienced memory B cells to secondary GCs is inefficient 38,39 , as the progeny of primed GC B cells account for only a subset of total GCBs.…”
Section: Discussionmentioning
confidence: 92%
“…(d) The timing of assessment. The two human studies on ipsilateral and contralateral boosting may have reached different conclusions because they evaluated antibody responses at different time points, ranging from two weeks to 14 months 22,23 . Analogously, the study in C57BL/6 mice with two homologous doses of BNT162b2 mRNA vaccine showed different affinity measurements at early and late time points after ipsilateral and contralateral boosting 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to anatomical sites used for the COVID-19 prime-boost vaccination series, two studies recently showed opposite effects with respect to ipsilateral vs. contralateral administration producing higher neutralizing titers. 11 , 12 Fazli et al. 12 hypothesized that the longer follow up time in their study (8–14 months vs. 2 weeks) may be responsible for the difference between the studies and speculated that ipsilateral delivery became preferable to contralateral delivery approximately 2–3 weeks after the second dose.…”
Section: Discussionmentioning
confidence: 97%
“… 11 showed that contralateral administration of the second dose in the primary series of COVID-19 mRNA vaccine is associated with lower neutralising titers compared to ipsilateral administration, Fazli et al. 12 recently showed the opposite. Similar comparisons have not been reported for ipsilateral vs. contralateral coadministration of influenza and COVID-19 vaccines on the same day.…”
Section: Introductionmentioning
confidence: 99%